2021
DOI: 10.1029/2021gl094276
|View full text |Cite
|
Sign up to set email alerts
|

Closure of the Paleo‐Asian Ocean in the Middle‐Late Triassic (Ladinian‐Carnian): Evidence From Provenance Analysis of Retroarc Sediments

Abstract: Asia is the largest extant accretionary continent that was constructed by the successive amalgamation of numerous continental blocks, magmatic arcs and subduction-accretion complexes from the Paleozoic to Cenozoic (Şengör, 1985; Şengör et al., 2018). The construction of the Central Asian Orogenic Belt (CAOB) that extends from the Ural Mountains in the west to the Pacific Ocean in the east involved the welding of major cratonic blocks viz. Siberia, Tarim, Alxa, and North China to form proto-Asia at the expense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…A study of a syn‐orogenic foreland basin's sedimentary provenance has been shown to be a valuable and dependable method for pinpointing the period of ocean closure and subsequent arc–continent collision (Bhattacharya, Robinson, & Wielicki, 2020). Song et al (2021) recently reported Triassic provenance changes in a foreland deposition (i.e., Middle Triassic sandstones were sourced from the NCC basement and a continental arc, whereas Late Triassic sediments received additional input from a juvenile arc) on the Alxa Block in northwest China, which marks the time of the final closure of the Palaeo‐Asian Ocean. In addition, the molasses sequence is widely accepted as indicating the conclusion of an orogeny cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of a syn‐orogenic foreland basin's sedimentary provenance has been shown to be a valuable and dependable method for pinpointing the period of ocean closure and subsequent arc–continent collision (Bhattacharya, Robinson, & Wielicki, 2020). Song et al (2021) recently reported Triassic provenance changes in a foreland deposition (i.e., Middle Triassic sandstones were sourced from the NCC basement and a continental arc, whereas Late Triassic sediments received additional input from a juvenile arc) on the Alxa Block in northwest China, which marks the time of the final closure of the Palaeo‐Asian Ocean. In addition, the molasses sequence is widely accepted as indicating the conclusion of an orogeny cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A study of a syn-orogenic foreland basin's sedimentary provenance has been shown to be a valuable and dependable method for pinpointing the period of ocean closure and subsequent arc-continent collision (Bhattacharya, Robinson, & Wielicki, 2020). Song et al (2021) Xiaohekou formations), suggesting that ultimate closure occurred before the late Triassic (Wang, Zhou, Wilde, Zhang, & Ren, 2016;Xin, Ren, Peng, & Sun, 2011;Zhou et al, 2017).…”
Section: Baiyanaobao Granitementioning
confidence: 99%
“…Early Palaeozoic magmatic rocks occur in the Inner Mongolia Uplift and the Xingmeng Orogenic Belt in the northern part of the NCC, and in the NQOB and the South Qinling Orogenic Belt in the southern part of the NCC. However, during the late Palaeozoic, the Xingmeng Ocean in the northern part of the NCC was closed (Zhang et al, 2007; Zhang et al, 2009), and the Xingmeng Orogenic Belt was rifted immediately after its closure (Shao et al, 2015) the Paleo‐Asian Ocean was still open and subducted beneath the NCC (Shen et al, 2019; Song et al, 2021; Zhang et al, 2021). The Mianlve Ocean in the southern part of the Qinling Orogenic Belt formed in the expansion stage during the late Palaeozoic (Dong, Zhang, Hauzenberger, et al, 2011, Dong, Zhang, Neubauer, et al, 2011; Dong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the study area, only nineteen samples are older than 543 Ma. beneath the NCC (Shen et al, 2019;Song et al, 2021;Zhang et al, 2021). The Mianlve Ocean in the southern part of the Qinling Orogenic Belt formed in the expansion stage during the late Palaeozoic Dong et al, 2016).…”
Section: Provenance Of Detrital Zircons In the Study Areamentioning
confidence: 99%
“…Ao et al (2021) identified the youngest matrix at 234 Ma in the Kanguer mélange, suggesting continuous northward subduction of the North Tianshan oceanic lithosphere in the late Triassic. By doing provenance exchange study, Abuduxun et al (2021), Song et al (2021), Bai et al (2020), and Chen et al (2020) suggested that there was only provenance exchange at the early to late Triassic in the South Tianshan orogen, Alxa block, and North Tianshan orogen, respectively, indicating closure of the corresponding oceans in the Triassic.…”
Section: Discussionmentioning
confidence: 99%